2009
DOI: 10.1002/ptr.2795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fenugreek Fiber on Satiety, Blood Glucose and Insulin Response and Energy Intake in Obese Subjects

Abstract: Eighteen healthy obese subjects participated in a single blind, randomized, crossover study of three test breakfasts, containing 0 g (control), 4 g or 8 g of isolated fenugreek fiber. Subjects recorded ratings of hunger, satiety, fullness and prospective food consumption using visual analog scales (VAS) every 30 min for 3.5 h. Postprandial blood glucose and insulin responses were measured. Energy intake from an ad libitum lunch buffet and for the remainder of the day was assessed. The 8 g dose of fenugreek fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 17 publications
1
83
1
7
Order By: Relevance
“…T. foenum-graeceum was reported to have hypoglycemic effects in rats as early as 1974 (Mishkinsky et al, 1974). In a study in diabetic patients, insulin levels were significantly higher in the T. foenum-graecum treatment group compared to the placebo treatment group (Mathern et al, 2009). Sharma et al, 1990, showed that the defatted seeds of T. foenum-graecum administered to Type 1 DM patients at a dose of 100g daily for 10 days significantly lowered fasting blood glucose, total cholesterol, low-density lipoproteins and tryglycerides (Sharma et al, 1990).…”
Section: Efficacy Of Traditional Herbal Medicines Used To Treat Diabementioning
confidence: 94%
“…T. foenum-graeceum was reported to have hypoglycemic effects in rats as early as 1974 (Mishkinsky et al, 1974). In a study in diabetic patients, insulin levels were significantly higher in the T. foenum-graecum treatment group compared to the placebo treatment group (Mathern et al, 2009). Sharma et al, 1990, showed that the defatted seeds of T. foenum-graecum administered to Type 1 DM patients at a dose of 100g daily for 10 days significantly lowered fasting blood glucose, total cholesterol, low-density lipoproteins and tryglycerides (Sharma et al, 1990).…”
Section: Efficacy Of Traditional Herbal Medicines Used To Treat Diabementioning
confidence: 94%
“…Mathern et al [29] has made studies on trend of food consumption in obese human beings and found that fenugreek fibre significantly increased satiety and reduced energy intake at lunch, suggesting that it may have short-term beneficial effects in obese subjects. Naidu et al (2011) [30] reported that fenugreek husk is a valuable source of dietary fiber and phenolic acids; therefore, it could be an effective source of natural antioxidants and natural ingredients in functional foods.…”
Section: Fenugreek Fibrementioning
confidence: 98%
“…The plant also represents a significant source of antioxidants (Naidu, 2011). In obese subjects, short-term beneficial effects of fenugreek fiber were reported on satiety, blood glucose, insulin response and energy intake (Mathern et al, 2009). In addition, fenugreek fiber can bind to and remove carcinogens in the intestine (Meghwal, 2012).…”
Section: Fenugreek Phytochemicals and Nutrientsmentioning
confidence: 99%
“…In male rabbits: decrease of testis weight, plasma concentration of androgens and sperm production Bin-Hafeez et al (2003) Leaves and seeds Reduction of perspiration, fever, allergies, bronchitis and congestion Faeste et al (2009) Seeds Treatment of sinus and lung congestion Singhal et al (1982) 26 Leaves and seeds Antimicrobial Sowmya and Rajyalakhsmi (1999) Leaves and seeds Treatment of hypertension and hypercholesterolemia Sowmya and Rajyalakhsmi (1999); Roberts (2012) Leaves and seeds Prevention of gas formation in digestive tract Mathern (2009) Steroids, flavonoids, alkaloids Raw material for hormones and pharmaceuticals Blank (1996) Leaves and seeds Antibacterial, anticancer, antiulcer, antinociceptive Sowmya (1999);Mathern (2009) Antifungal activity on Candida albicans, C. glabrata and C. tropicalis Sautor (2004) Inhibition of replication of hepatitis C virus (HCV) Wang (2011) Decrease of glycaemia and intestinal disaccharidases in vivo…”
Section: Diosgeninmentioning
confidence: 99%